Priority values survey in different men's sports - Vostroknutova, T.F.; Vostroknutov, S.I.; Savelyeva, M.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to survey and analyze priority values specific for different men's sports. Methods and structure of the study. We sampled for the survey three groups of athletes (n=90) representing the following men’s sports: Group 1 (G1): martial artists (n=30); Group 2 (G2): cyclists (n=30); and Group 3 (G3): fitness club members (n=30). The priority values of the sample were rated by the M. Rokeach Human Values survey method [4], with the test data processed by the rank distribution analysis to obtain terminal/ goal values. To obtain significant survey data, we requested the sample to rank the presently relevant “real” values, and then the desired "ideal" values. We provisionally grouped the 18 priority values ranks into (1) priority values module: ranks 1 to 6; (2) neutral values module: ranks 7 to 12; and (3) rejected values module: ranks 13 to 18. Results and conclusion. Our survey and analysis of the sport-specific priority values in a few men's sports give grounds for the following conclusions: - Two types of the M. Rokeach rank distribution for “real” and “ideal” priority values were found beneficial for the individual priority values differentiation and analyzing purposes; – The modular priority value structure in three sports groups was found virtually identical that may be interpreted as indicative of the similar social and vocational worldviews with the set of specific, private, interpersonal and activity values; and - Rankings of the values in transition from the real to ideal ones were found to change towards the private life related values, including the adaptive ones.